Sectors of liguleless-1 tissue interrupt an inductive signal during maize leaf development. - Becraft, P W (1991)
The ligule and auricles separate the blade and sheath of normal maize leaves and are absent in liguleless-1 (lg1) mutant leaves. We induced chromosome breakage using X-rays to create plants genetically mosaic for lg1. In genetically mosaic leaves, when an lg1 mutant sector interrupts the normal ligule, the ligule is often displaced basipetally on the marginal side of the sector. Therefore, lg1 mutant sectors not only fail to induce ligule and auricle, but are also disrupting some form of intercellular communication that is necessary for the normally coordinated development of the ligular region. Our data are consistent with a model in which an inductive signal originates near the midvein, cannot traverse the lg1 mutant sector, and reinitiates in the wild-type tissue across the sector toward the leaf margin. The lg1 gene product, therefore, appears to be required for the transmission of this signal and could be involved with reception.